Inovasi Produk Pangan Lokal “Nutribites” Sebagai Upaya Pencegahan Stunting Pada Anak Usia Dini - Dewi Aisyah Widiawati; Dione Nabila Jang Putri; Dwi Atika; Fadhila Alif Aulia; Fida Mauliyatul Chusnia; Fizah Taswirul Bariroh; Ikke Nurroani; Intan Cahyani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Chronic nutritional conditions such as stunting are still a problem that requires special attention in Indonesia, because they can hinder children's growth and intelligence. One solution that can be developed is to provide nutritious local food products that are practical and popular with children. This research discusses the " Nutribites" product, a healthy snack made from local ingredients such as Moringa leaves, snakehead fish, mocaf flour (modified cassava flour), gelatin, and date puree. This research was carried out through a literature review by analyzing various scientific sources that discuss the nutritional content and benefits of the ingredients that make up the product. Studies conducted show that the mixture of ingredients in Nutribites has complete nutritional content, including protein, calcium, iron and vitamins, which are very much needed to support children's growth, especially in the early phases of life. Apart from being high in nutrition, this product also has social and economic potential because it can be developed as a community-based business. Thus, Nutribites can be an alternative nutritious snack based on local food that contributes to preventing stunting while supporting the implementation of the SDGs agenda, especially the second goal which focuses on eliminating hunger and the third goal which emphasizes the importance of community health and welfare.